Prevalence of human papillomavirus in the saliva of sexually active women with cervical intraepithelial neoplasias - Sánchez-Siles, Mariano (Med Oral Patol Oral Cir Bucal, 2020)
BACKGROUND: The main objective of this study was to estimate the prevalence of human papillomavirus-DNA (HPV-DNA) in the saliva of sexually active women with HPV-related cervical intraepithelial neoplasias (CIN) and compare the findings with a healthy control group. The secondary objectives were: 1) to determine the concordance between genital and oral HPV types in sexually active women with HPV-related CIN; 2) to analyze whether sexual habits influence the presence of HPV-related CIN; 3) to determine whether sexual habits influence the presence of oral HPV. MATERIAL AND METHODS: Saliva samples were collected from 100 sexually active women, 50 with HPV-related CIN and 50 healthy subjects presenting normal cytology. PCR assay was used to detect HPV-DNA. RESULTS: The prevalence of oral HPV infection in saliva samples was 14% in women with HPV-related CIN, while in the healthy group it was 12%, without statistically significant difference (p =0.766). As for the concordance between genital and oral HPV types in women with HPV-related CIN, concordance was only observed for HPV-16, whereby among 22 women with genital HPV-16, only one (4.54%) also presented oral HPV-16. Regarding the possible influence of sexual habits on the presence of cervical pathology and presence of oral HPV, it was found that marital status, age at first intercourse, number of lifetime sexual partners, and condom use are related with the presence of cervical pathology (p<0.001; p=0.017; p=0.002; and p <0.001, respectively); condom use was also found to be related to the presence of oral HPV (p<0.001). CONCLUSIONS: The prevalence of HPV-DNA in the saliva of sexually active women with HPV-related CIN is similar to healthy women. The concordance between genital and oral HPV types is low. Both the presence of cervical pathology and the presence of oral HPV are related to sexual habits. Wider sample size is required to confirm this results. Key words:Cervical intraepithelial neoplasias, HPV, saliva, cervix, cancer.